Analysis of Anthelmintic Agents, Indications for Their Use and Disadvantages Associated (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Helminths are a group of parasites that are producing serious health issues for animals all over the world. Pharmaceutical anthelmintics have been the mainstay of helminthiasis control. Unfortunately, a significant and striking degree of anthelmintic resistance has resulted from the overuse of anthelmintic medications. A heritable loss of anthelmintic sensitivity in a parasite population that was previously susceptible to the same anthelmintic is known as anthelmintic resistance. Almost all animal species' helminths and various anthelmintic groups across many continents exhibit signs of developing anthelmintic resistance. Anthelmintic resistance is predisposed by the parasite's genetics, underdosing, frequent therapy, and the timing and targeting of mass treatment. The primary mechanisms of anthelmintic resistance include upregulation of cellular efflux mechanisms, increased drug metabolism, altered drug receptor sites that decrease drug binding or the functional effects of drug binding, and decreased drug receptor abundance due to decreased expression within the parasite. Anthelmintic resistance can be found using in vitro techniques like PCR, egg hatch assays, larval mobility tests, and larval development tests, as well as in vivo techniques like the fecal egg count reduction test. The development of anthelmintic resistance can be slowed down by utilizing anthelmintic medications appropriately, combining anthelmintic medications, and using alternate methods. Given that anthelmintic resistance is a major global issue, it is important to use the current anthelmintics appropriately and lessen reliance on them in order to lessen the problem.